The Innate Alarm System and Subliminal Threat Presentation in Posttraumatic Stress Disorder: Neuroimaging of the Midbrain and Cerebellum. (January 2019) - Terpou, Braeden A.; Densmore, Maria; Thome, Janine; Frewen, Paul; McKinnon, Margaret C.; Lanius, Ruth A.
Background: The innate alarm system, a network of interconnected midbrain, other brainstem, and thalamic structures, serves to rapidly detect stimuli in the environment prior to the onset of conscious awareness. This system is sensitive to threatening stimuli and has evolved to process these stimuli subliminally for hastened responding. Despite the conscious unawareness, the presentation of subliminal threat stimuli generates increased activation of limbic structures, including the amygdala and insula, as well as emotionally evaluative structures, including the cerebellum and orbitofrontal cortex. Posttraumatic stress disorder (PTSD) is associated with an increased startle response and decreased extinction learning to conditioned threat. The role of the innate alarm system in the clinical presentation of PTSD, however, remains poorly understood. Methods: Here, we compare midbrain, brainstem, and cerebellar activation in persons with PTSD (n = 26) and matched controls (n = 20) during subliminal threat presentation. Subjects were presented with masked trauma-related and neutral stimuli below conscious threshold. Contrasts of subliminal brain activation for the presentation of neutral stimuli were subtracted from trauma-related brain activation. Group differences in activation, as well as correlations between clinical scores and PTSD activation, were examined. Imaging data were preprocessed utilizing the spatially unbiased infratentorial template toolbox within SPM12. Results: Analyses revealed increased midbrain activation in PTSD as compared to controls in the superior colliculus, periaqueductal gray, and midbrain reticular formation during subliminal threat as compared to neutral stimulus presentation. Controls showed increased activation in the right cerebellar lobule V during subliminal threat presentation as compared to PTSD. Finally, a negative correlation emerged between PTSD patient scores on the Multiscale Dissociation Inventory for the Depersonalization/Derealization subscale and activation in the right lobule V of the cerebellum during the presentation of subliminal threat as compared to neutral stimuli. Conclusion: We interpret these findings as evidence of innate alarm system overactivation in PTSD and of the prominent role of the cerebellum in the undermodulation of emotion observed in PTSD.